Analisis Pengaruh Struktur Aktiva, Tingkat Pertumbuhan Dan Profitabilitas Terhadap Struktur Modal Perusahaan-Perusahaan Makanan Dan Minuman Yang Go Public Di Bursa Efek Indonesia - Susiani Susiani (BIP's JURNAL BISNIS PERSPEKTIF, 2013)
One of importont decisions on financial management is financing decision. The decision will be contact with how to determine the optimal capital structure. On these problem, each of financial manager very necessary to make consideration about factors will be influence of capital structure. The objective of the research is to analyze the influence of factors, among other things : asset structure, growth rate and profitability of the firms. Population of this research are all of food & beverage company listed at Bursa Efek Indonesia (BEI). The sample includes ten companies registered at BEI. The data analysis instrument employed was multiple regression analysis, Flest and t-test. The results of the research indicate that the factors of the capital structure determiners which have significant effect on capital structure, according to simultantly are assets structure, growth rate and profitability. And according to partially that only profitability which have significant effect on capital structure, but assets structure and growth rate which do not give significant effect on capital structure.